E-Waste: Current Research and Future Perspective on Developing Countries - Halim, L.; Suharyanti, Y. (International Journal of Industrial Engineering and Engineering Management, 2019)
Increase of population, purchasing power, and development of technology give consequence to Waste of Electronic and Electrical Equipment (WEEE) or e-waste generation. Increasing rate of e-waste production and its hazardous content raise the concern regarding e-waste. This paper aims to describe the research development on e-waste in various countries and propose the perspective of future research. The study based on literature survey in open access journals using â€˜e-wasteâ€™ as the keyword. Article selection was done by considering the reputability of the source and cited frequency. From the articles reviewed, China contributed to most of the researches. Some of most studied topic namely e-waste management, e-waste impact to human health and environment and current status of e-waste treatment in specific country. Brief explanation on each topic and insight on future research are also provided.Â